Synthesis of silver nanoparticles using chemical reduction techniques for Q-switcher at 1.5 Î¼m region - Lokman, Muhammad Quisar; Mohd Rusdi, Muhammad Farid; Aiman Rosol, Ahmad Haziq; Ahmad, Fauzan; Shafie, Suhaidi; Yahaya, Hafizal; Mohd Rosnan, Rizuan; Abdul Rahman, Mohd Azizi; Harun, Sulaiman Wadi (Elsevier, 2021)
This research investigated the generation of passively Q-switched erbium (Er)-doped fibre laser using silver nanoparticles/poly (vinyl alcohol) (Ag/PVA) as a saturable absorber (SA). The Ag nanoparticles were synthesised via the chemical reduction technique. The Ag/PVA film based SA was fabricated by blending Ag nanoparticles powder into the PVA suspension, then left to dry at ambient to develop a free-standing SA film. Next, the Ag/PVA film was sandwiched in between two FC/PC fibre ferrules and integrated into the laser cavity for Q-switched pulse generation. The result shows that the Q-switched pulsed laser achieved pulse energy and peak power of 128.04 nJ and 21.34 mW at the maximum pump power of 107.1 mW. A signal-to-noise ratio (SNR) value of 66.23 dB was obtained at a frequency of 66.23 kHz proving that it is an excellent candidate as a SA material for Q-switched generation in future large-scale manufacturing.